A catalogue of periodic fully-resonant azulene-transitive azulenoid tilings analogous to Clar structures - Brinkmann, Gunnar (Array, 2009)
Summary: A reference catalogue of 1274 fully-resonant azulenoid tiling patterns with a symmetry group that operates transitively on the azulenes has been generated, and may be consulted at http://caagt.ugent.be/azul. Such networks are analogous to Clar structures and fully-naphthalenoid structures among benzenoids